BOGOR CITY REGIONAL REGULATIONS NUMBER 17 OF 2019 CONCERNING CULTURAL HERITAGE - Shariel, Muhammad Fariza; Yusuf, Muhammad Arsjad (Fakultas Hukum Universitas Djuanda, 2024)
n this era of modernization, people are very indifferent to the existence of historical buildings and cultural heritage sites, all because people think that old buildings have no value and have been replaced by new, more modern buildings. This research aims to determine the implementation of Bogor City Regional Regulation Number 17 of 2019 using the method used by reading and looking at the condition of cultural heritage in Bogor City. This research is empirical juridical research. Results: Implementation of Bogor City Regional Regulation Number 17 of 2019. Cultural heritage in the form of objects, buildings, structures, sites and areas needs to be managed by the government and regional governments by increasing community participation to protect, develop and utilize cultural heritage. The government's efforts in managing and maintaining cultural heritage sites are still not optimal, even though the government has taken steps to review efforts to protect cultural heritage sites, namely by establishing policies that can overcome acts of destruction. . However, the existence of this policy is still not enough to overcome this problem because there are still strong factors that cause the lack of strong legal protection for cultural heritage sites.